Poly(3-hexylthiophene) nanoparticles for biophotonics: study of the mutual interaction with living cells. Issue 3 (22nd December 2016) - Zucchetti, Elena; Zangoli, Mattia; Bargigia, Ilaria; Bossio, Caterina; Di Maria, Francesca; Barbarella, Giovanna; D'Andrea, Cosimo; Lanzani, Guglielmo; Antognazza, Maria Rosa
Abstract : Poly(3-hexylthiophene) nanoparticles interfacing with living cells: a new tool for biophotonics applications. Abstract : We report on the mutual interaction between poly(3-hexylthiophene) nanoparticles (P3HT-NPs) and human embryonic kidney (HEK-293) cells. P3HT-NPs, prepared in sterile conditions and efficiently uptaken within the live cells cytosol, show well-ordered morphology, high colloidal stability and excellent biocompatibility. Electrophysiology and calcium imaging experiments demonstrate that physiological functions of live cells are fully preserved in the presence of P3HT-NPs. From a complementary point of view, the photophysical properties of P3HT-NPs are also mainly maintained within the cellular environment, as proven by in situ time-resolved photoluminescence. Interestingly, we detect slight modifications in emission spectra and dynamics, which we ascribe to the contribution from the P3HT-NPs surface, possibly due to conformational changes as the result of the interaction with intracellular proteins or the formation of NPs aggregates. This work demonstrates that P3HT-NPs are excellent candidates for use as light sensitive actuators, due to their remarkable physical properties, optimal biocompatibility and capability of interaction with living cells.